2019
DOI: 10.1371/journal.ppat.1007944
|View full text |Cite
|
Sign up to set email alerts
|

Alternative conformations of a major antigenic site on RSV F

Abstract: The respiratory syncytial virus (RSV) fusion (F) glycoprotein is a major target of neutralizing antibodies arising from natural infection, and antibodies that specifically bind to the prefusion conformation of RSV F generally demonstrate the greatest neutralization potency. Prefusion-stabilized RSV F variants have been engineered as vaccine antigens, but crystal structures of these variants have revealed conformational differences in a key antigenic site located at the apex of the trimer, referred to as antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…54 A recent report of two new site Ø mAbs with different RSV A and B specificities also highlighted the structural variations of this antigenic site. 45 Among the isolated highly potent mAbs in this study, we indeed found that mAbs targeting site Ø showed the most variations in neutralization potencies between the two different RSV subtypes, including a strain A-specific mAb 139B8. Similar mAbs were also reported previously from immunized mice and from human adults.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…54 A recent report of two new site Ø mAbs with different RSV A and B specificities also highlighted the structural variations of this antigenic site. 45 Among the isolated highly potent mAbs in this study, we indeed found that mAbs targeting site Ø showed the most variations in neutralization potencies between the two different RSV subtypes, including a strain A-specific mAb 139B8. Similar mAbs were also reported previously from immunized mice and from human adults.…”
Section: Discussionmentioning
confidence: 54%
“…Critical residues identified for antibody binding were labeled and color-coded according to the corresponding antigenic sites. and IV binding mAbs 36,45,47 and extends to additional antigenic sites (III and V). Our data exemplified the diversity of anti-RSV mAbs and provided novel understanding into immune recognition mechanisms of RSV.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, residues after K187 in the C-terminal region of the CCD also appear to be flexible. Thus, RSV G is part of a growing list of antigens with flexible or intrinsically disordered regions (IDRs) that are targeted by antibodies (48)(49)(50)(51)(52)(53)(54)(55)(56). The observation of different conformations of the RSV G CCD raises several important questions.…”
Section: Discussionmentioning
confidence: 99%
“…Structures of F proteins complexed with neutralizing antibodies have been solved for a number of pneumo-and paramyxovirus family members including RSV (Figure 3), HPIV3, and NiV. Distinct antigenic sites were identified on RSV F (Figure 4): conformation-dependent site Ø that is located at the apex of prefusion F and a dominant target for nAbs [36,[76][77][78]; sites II and IV that are present in both the pre-and postfusion F conformations [67,79]; site III that likewise exists in both F conformations, but undergoes rearrangement of secondary structure elements forming the epitope [80,81]; site V located between sites Ø and III on prefusion F [82,83]; and post-fusion F site I [84,85]. A cryo-EM structure of HPIV3 F complexed with nAb PIA174 likewise locates the binding site to the apex of the prefusion F trimer, establishing contact with residues of all three F protomers [37].…”
Section: Druggable Sites and Neutralizing Epitopesmentioning
confidence: 99%